Toxic Effect of Topical DLBS1425 Towards Proliferation Degree and Mucin Secretion in Rabbit’s Eye - Amy Aurelian; Trilaksana Nugroho; Dina Novita (Majalah Oftalmologi Indonesia, 2016)
Background: Phaleria macrocarpa (DLBS1425) is a medicinal plant that has the effects of anti-cancer, anti-inflammation, anti-angiogenesis, and antioxidants. The potency of its toxicity is low towards normal cell. DLBS1425 is expected to be useable for eye drop, but its toxic effect towards goblet cell proliferation and mucin secretion still remain unknown.Methods: This is experimental study with design of comparison test. Twenty four rabbits’ eyes divided into 4 groups were given placebo and topical DLBS1425 with concentration of 1×10-1 mg/ml, 1×100 mg/ml, and 1×101 mg/ml. Goblet cell proliferation degree and mucin secretion were evaluated using histopathology examination from rabits’ conjunctiva.Results: In the group of goblet cell proliferation, compared to control group, there was decreased proliferation degree with topical DLBS1425 of 1×10-1 mg/ml; but the concentration of 1×100 mg/ml and 1×101 mg/ml did not affect goblet cell proliferation. In the group of mucin secretion, DLBS1425 with any concentration level decreased mucin secretion significantly.Conclusion: There was significant difference in goblet cell proliferation with topical DLBS1425 of 1×10-1 mg/ml and placebo. There was also significant difference in mucin secretion with topical DLBS1425 in any concentration level and placebo. Keywords: DLBS1425, goblet cell, mucin secretion